A reflection of Divine-based Islamic Economics (D-BIE) - Hamat, Mustapha; Haneef, Mohamed Aslam; Mohammed, Mustafa Omar; Kassim, Salina (IIUM Press, 2023)
The troubling issue leading to undertaking this research is the increasing frequency of economic crises with widespread and severe effects. Despite introducing and implementing several measures, the problem continues. Among the steps, Divine-based Islamic economics is promising but challenging. The main challenge is that the current economic system has yet to command the trust and confidence of political masters, policymakers, and people. Previous studies have presented convincing theoretical arguments supporting introducing and implementing a Divine-based Islamic economic system. However, the current Islamic economic model is not scientifically valid; no empirical evidence shows that it is superior to the existing secular economic systems. However, acceptability could have been better. This study argues that constructing a user-friendly prototype conceptual model is critical for gaining and enhancing trust and confidence in the system.